Grud'yu na zashchitu Petrograda! - Apsit, Aleksandr (Плакат СССР (Plakat), 1919)
Red army soldiers, sailors and civilians forming a line holding rifles with Petrograd in background Original title: Грудью на защиту Петрограда! PO-1208